1982
DOI: 10.3354/meps008233
|View full text |Cite
|
Sign up to set email alerts
|

Ecological Growth Strategies in the Seaweeds Gracilaria foliifera (Rhodophyceae) and Ulva sp. (Chlorophyceae): Photosynthesis and Antenna Composition

Abstract: Observations have been made on photosynthesis (oxygen evolution) and seasonal fluctuations in antenna pigments in 2 seaweeds which CO-occur in the vicinity of Beaufort, North Carolina, USA. Gracilaria foljifera (Rhodophyceae) and Ulva sp. (Chlorophyceae) were grown in outdoor continuous-flow cultures a t ambient incident light (I,) and .13I,. Pigment contents and accessory pigment: chlorophyll a ratios were higher at ,131, than at I,. Total pigment levels were correlated with soluble N in seaweed tissue. Durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
2
2

Year Published

1987
1987
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(31 citation statements)
references
References 15 publications
2
25
2
2
Order By: Relevance
“…The highest concentrations were recorded in the months with lowest sunlight (July, August, May and June) and the lowest in the months with elevated sunlight levels (December, January and February). These variations are similar to those described by other authors, who reported an increase in total soluble proteins and phycobiliproteins in winter and a drop in summer (Kosovel & Talarico, 1979;Rosenberg & Ramus, 1982;Campbell et al, 1999;Aguilera et al, 2002;Orduña-Rojas et al, 2002). In this study, the association between high protein and pigment concentrations, lower solar irradiance and high nitrogen concentrations was clear.…”
Section: Discussionsupporting
confidence: 79%
“…The highest concentrations were recorded in the months with lowest sunlight (July, August, May and June) and the lowest in the months with elevated sunlight levels (December, January and February). These variations are similar to those described by other authors, who reported an increase in total soluble proteins and phycobiliproteins in winter and a drop in summer (Kosovel & Talarico, 1979;Rosenberg & Ramus, 1982;Campbell et al, 1999;Aguilera et al, 2002;Orduña-Rojas et al, 2002). In this study, the association between high protein and pigment concentrations, lower solar irradiance and high nitrogen concentrations was clear.…”
Section: Discussionsupporting
confidence: 79%
“…Harris 1978; Rosenberg and Ramus 1982;Porter 1980;Porter et al 1984). We suggest two ways that light saturation parameters for a whole community can increase.…”
Section: Discussionmentioning
confidence: 99%
“…phycoerythrin and phycocyanin) contents of E. elongata were not influenced by carbon and nitrogen treatment, contrary to previous studies: in Gracilaria spp. phycoerythrin increased with seawater N concentration and internal N content (Rosenberg & Ramus 1982, Figueroa et al 2010). On the other hand, Gao & Zheng (2010) observed a decrease in the phycoerythrin content of Corallina sessilis when exposed to high CO 2 (1000 ppmv) for 30 d. The short experimental duration of the present study may explain the lack of change in phycobiliprotein levels.…”
Section: Pigmentsmentioning
confidence: 99%